Językoznawca jako badacz mediów (zarys problematyki) - Wojtak, Maria (Poznańskie Spotkania Językoznawcze, 2015)
The author presents the proceedings used by the linguists involved in the media research highlights dominant approaches, distinguishes two hypothetical ones: hegemonic and sovereign, and discusses challenges related to both of them. Hegemonic approach in the media research means the a distinctly defined subject of the study, that is the language of the media, precisely defined subject of analysis, namely the language of the media, and a supremacy of linguistic methods used in the analysis. The linguist as a sovereign prefers an open attitude towards methods applied in the study. Such an approach considers achievements of the media scholarshop as well as other related scientific disciplines. This attitude in the media research means that the linguist analyzes an image of the world in the media, a stylistic differentiation of the media communication, media genres, and the discourse. Furthermore, the linguist as a sovereign claims creating a new linguistic discipline and widens the research field with contrastive issues.